Causality Analysis of Economic Growth, Inflation, and Interest Rates on the Jakarta Composite Index (JCI) in Indonesia: An ARDL Approach - Meisya Diazzahra Putri Basudewa; Asep Munir Hidayat; Billy Tejaarief; Kenedi Kenedi; Anti Wulan Agustini (Transpublika Publisher, 2025)
One important indicator of Indonesia's economic condition is the Jakarta Composite Index (JCI). As the measure of all listed stocks, its movement directly reflects economic stability and investor confidence. The JCI is, however, highly susceptible to both global and domestic macroeconomic pressures, making its relationship with key fundamentals, such as economic growth, inflation, and interest rates. The purpose of this study is to analyze the short-term and long-term impacts of inflation, interest rates, and economic growth on the JCI. This study uses the Autoregressive Distributed Lag (ARDL) model on time series data using secondary data and quantitative correlation techniques. The results show that although economic growth has no short-term impact on the JCI, it does have a significant long-term impact. On the other hand, neither inflation nor interest rates have a significant impact on the JCI in the short or long term. An adjustment rate of 50.49% was achieved using an error correction mechanism, indicating a tendency towards long-term equilibrium. Additional causality analysis shows a unidirectional relationship between inflation and the JCI and between the JCI and economic growth. However, neither the JCI nor interest rates and economic growth have a reciprocal relationship on the JCI, and there is no causal relationship between the both.